Assessing the innovation capability of small- and medium-sized enterprises using a non-parametric and integrative approach - Castela, B.; Ferreira, F.; Ferreira, J.; Marques, C. (Management Decision, 2018)
Purpose: The aftermath of the recent financial crisis has shown that the ability to innovate is a vital management skill and that the methodologies used to evaluate innovation capability within small- and medium-sized enterprises (SMEs) should be as holistic and integrative as possible. The purpose of this paper is to address this issue through the combined use of cognitive mapping and the analytic hierarchy process (AHP). Design/methodology/approach: Cognitive mapping and multiple criteria decision analysis have proved over the years to be effective in handling a wide range of complex decision problems. Following a socio-technical approach, a non-parametric method of evaluating SME innovation capability – based on the results of group meetings with a panel of information technology entrepreneurs and SME chief executive officers – was created, tested and validated. Findings: The methodological processes adopted in this study provide promising results for decision makers seeking to identify the most innovative SMEs. Furthermore, the sensitivity analyses carried out also supported the findings. Research limitations/implications: This study confirms the usefulness of integrating cognitive mapping and the AHP to facilitate evaluations of SME innovation capability. However, due to the process-oriented nature of the research, extrapolations without proper adjustments are not recommended. Practical implications: The panel members who participated in this study consider the proposal extremely versatile and see great potential for further applications in the measurement of SME innovation capability. Originality/value: The combined use of cognitive mapping and the AHP offers a holistic and well-informed perspective on the issue in question. The authors know of no prior work reporting this approach in the same research context.